2018
DOI: 10.2147/cmar.s167774
|View full text |Cite
|
Sign up to set email alerts
|

Young age increases the risk of lymph node positivity in papillary thyroid cancer patients: a SEER data-based study

Abstract: IntroductionCurrently in papillary thyroid cancer (PTC), the correlation between lymph node positivity (LN+) and patient’s age at diagnosis is still inconclusive. The aim of this study was to investigate whether younger PTC patients had higher LN+ rates.Patients and methodsFrom the 1998–2013 Surveillance, Epidemiology, and End Results database, we analyzed PTC patients with at least 1 LN examined. The patients were divided into 5 groups by age separately for each T stage: ≤30; 31–40; 41–50; 51–60; >60 years.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 46 publications
9
35
0
Order By: Relevance
“…Compared with patients with older ages, patients with younger ages usually had tumors with higher malignancy or more aggressive histological features, which might ultimately lead to a higher tendency to liver metastasis or other forms of distant metastases. 22,23 Consistent with studies of other kinds of tumors, Chang et al reported that early onset patients were much more vulnerable to positive circumferential margins, venous invasion and perineural invasion in colorectal adenocarcinoma. 24 Multiple genetic alterations in younger patients also supported the hypothesis that tumor cells in the young were more susceptible to promoting DNA damage than in the old.…”
Section: Discussionsupporting
confidence: 59%
“…Compared with patients with older ages, patients with younger ages usually had tumors with higher malignancy or more aggressive histological features, which might ultimately lead to a higher tendency to liver metastasis or other forms of distant metastases. 22,23 Consistent with studies of other kinds of tumors, Chang et al reported that early onset patients were much more vulnerable to positive circumferential margins, venous invasion and perineural invasion in colorectal adenocarcinoma. 24 Multiple genetic alterations in younger patients also supported the hypothesis that tumor cells in the young were more susceptible to promoting DNA damage than in the old.…”
Section: Discussionsupporting
confidence: 59%
“…Similar to our study, Andrew et al [20] found that the ipsilateral central LNM risk related to age was U-shaped with increased odds of metastases in younger and older patients. The number of cases analyzed in these studies [22] and showed that younger patients had an increased LNM risk regardless of T stage. However, since patients were grouped based on 10-yearly age increments, it was impossible for them to infer that LNM can disappear spontaneously with delayed surgery in immune competent young and middle-age patients.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies [18][19][20][21][22] have examined the association between patient age at diagnosis and LNM in PTC, but the conclusions have been inconsistent. A single institution study of 1226 patients with PTMC [18] demonstrated that middle-aged and elderly patients had a lower risk of LNM compared with young patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with muscle-invasive bladder urothelial carcinoma (MIBC), the evaluation of LN+ is very important for staging and decisions on treatment. Age is an independent predictor of LN+ in various cancers [ 7 9 ]. In an analysis of 46,077 patients with thyroid cancer, it was found that young patients were more likely to have LN+, regardless of the T stage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%